Patients & Tumor Characteristics - TAHA, D E A; Elhaj, AM; Elshiekh, A A (Gezira Journal of Health Sciences; Vol 3 No 2 (2007), 2007)
Among the breast cancer population in the institute of Nuclear Medicine, Molecular Biology and Oncology (INMO) in central Sudan, it was found that the incidence is more frequent among young women especially among those who are 40 years old or younger at presentation. Abnormal body mass index was found in the majority of the population of this study. Although gynaecological and obstetrical history was found to be insufficiently recorded in the patients folders, there was high percentage of women who had never conceived (38.2%) among those who have between 0-3 children (70%) which is known to be associated with increased risk for breast cancer . Family history of breast cancer among this group of patients (4.9%) is comparable to the internationally published figures. There was no specification mentioned on the histopathology report for tumour grade for 52% of the study population, for lymphovascular invasion for 85.3% of the study population, and for oestrogen receptor status for 86.3% of the study population, which made comment on the distribution of these important factors among the study group rather irrelevant although it appeared that high grade tumors is not infrequent among the study group. Also of note on this point that the quality of the histopathology report, which is almost always not containing the relevant information for treatment decisions and prognostication, is hindering good clinical practice and following the international management guidelines. Disease stages iiia, iiib, and vi comprised the majority of the stages among the study population and it clearly reflects the late presentation that this group of patients had.